A problem of industries and regions: unemployment and structural change in Britain during the interwar years and 1980s - Paker, M (2021)
The most serious employment crises in twentieth-century Britain occurred during the interwar years and the early 1980s, when, in both cases, the unemployment rate climbed to over 10% in aggregate and remained high for many years. Both downturns also coincided with periods of structural change in the economy: in the interwar years, export-oriented heavy industries lost out to expanding light manufacturing industries, and, during the early 1980s, the decline of manufacturing accelerated as the economy pivoted toward service industries and finance. A large literature on these recessions has dealt with aggregate demand fluctuations and supply factors, but this mainly macroeconomic focus has limited our understanding of the impacts of structural change. This thesis investigates the interaction of structural change and the business cycle in both the crises using newly-digitized industry microdata and econometric methods. How did structural change affect these employment downturns, and what were the consequences for workers and the labor market? I find that in both periods, secular structural change contributed significantly to, and was amplified by, the cyclical downturn. This interaction caused the im- pact of the interwar and early 1980s recessions to vary across industries, regions, gender, and demographic groups, with some workers experiencing persistent disadvantage.